Statistical analysis of the development indicators' impacts on e-commerce of individuals in selected European countries - Ksenija Dumičić; Ivana Skoko Bonić; Berislav Žmuk (Naše gospodarstvo / Our Economy, 2018)
The aim of this paper is to analyse the influence of the development level indicators on the e-commerce, i.e. on the online purchase by individuals, in selected European countries in 2013. In the analysis, the main variable under study and all the independent variables are included as standardised. Based on nine variables, the principal component analysis with varimax rotation was performed and the two extracted factors were used as the regressors in the multiple regression analysis. In the regression model both components, Factor 1, which includes seven variables, called Prosperity, Investing in Education and IT Infrastructure, and Awareness, and Factor 2, comprised of two variables, called IT Skills, are statistically significant at the significance level of 1%. Both factors show a positive correlation with the online purchase of individuals. Inclusion and analysis of distributions and impacts of even nine independent variables, which make up two distinct factors affecting the e-commerce, make a new contribution of this work.
Keywords: C38; L81; 330; e-commerce; broadband access to the Internet; factor analysis; multiple regression analysis